2010
DOI: 10.5120/421-621
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Higher Order Metrics for SPIHT Based Image Compression

Abstract: The increasing use of digitized images has led to the need to compress such imagery to allow economical storage and fast data transfer. Despite all the advantages of JPEG compression schemes based on DCT namely simplicity, satisfactory performance, and availability of special purpose hardware for implementation; these are not without their shortcomings. The input image needs to be blocked which results in noticeable and annoying blocking artifacts particularly at low bit rates. So over the past several years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Jindal et al compared the SPIHT coding method with the JPEG and wavelet transform coding methods using higher order metrics via skewness and kurtosis. They found that the SPIHT algorithm performed better at lower bit rates and skewness, where as JPEG was found to have better kurtosis [10].…”
mentioning
confidence: 99%
“…Jindal et al compared the SPIHT coding method with the JPEG and wavelet transform coding methods using higher order metrics via skewness and kurtosis. They found that the SPIHT algorithm performed better at lower bit rates and skewness, where as JPEG was found to have better kurtosis [10].…”
mentioning
confidence: 99%